(untitled) (Research, Society and Development, 2020)
The article contextualizes the contemporary debate about Human Rights, making a historical recovery of how this theme is treated in different Constitutions and identifies its socio-cultural implications in the Communication and Information Society - ICTs. The proposal consists in verifying whether the insertion of educommunicative practices, as a pedagogical resource, provides training aimed at the promotion and preservation of Human Rights, so necessary for the development of citizenship and social justice. ICTs have evolved exponentially, which allows individuals to be connected through internet networks, providing greater visibility of human behavior. However, they sometimes cause serious violations of fundamental rights, given the deterritorialization and speed of information conveyed by social networks. For this, the deductive approach and monographic procedure methods were used. As research techniques, bibliographic and documentary research was used. Finally, it is highlighted that the educommunicative practices are essential to think and develop an education for and in Human Rights, both in formal and non-formal teaching environments.